Blowfly Larval Tissues as a Secondary Detector for Determining Paraquat-Related Death in Rabbit Carcass - Lawai, Vannessa; Abdul Rahim, N.A; Zainab, Ngaini (Blackwell Publishing Inc., 2015)
Paraquat poisoning is commonly associated with suicide or homicide in Malaysia. In a case involving advanced body decomposition, pathological analysis regarding the cause of death may become difficult or almost impossible. Insects serve as common alternative matrix for poison detection in forensic analysis. Paraquat detection via secondary bioaccumulation in fly larvae tissue has never been reported. In this study, tissues from blowfly larvae collected from a rabbit carcass with paraquat poisoning were analyzed for secondary bioaccumulation. Larvae samples were collected and analyzed using liquid-liquid extraction. The detection was performed via reduction of quaternary ammonium presence in paraquat and analyzed using gas chromatography-mass spectrometry (GC-MS) with selected ion monitoring mode (SIM mode). GC-MS showed the elution of reduced paraquat was at retention time 12.8min. Blowfly larvae tissue has proven useful as a secondary detector in paraquat-related deaths.